ANALISIS SISTEM ANTRIAN PADA LOKET PENGURUSAN KARTU TANDA PENDUDUK (KTP) DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MUNA BARAT - Fitriani Fitriani; La Hatani; Sinarwaty Sinarwaty; Endro Sukotjo; Adnan Hakim (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims to queuing analysis the card registrar at the resident service office and civil adminitration in the district Muna Barat. This research uses QM For Windows 5.2 software application with Waiting Lines analysis tool. Waiting Lines is used to process the queue, either queue of people or goods. This type of research is descriptive statistics with a qualitative approach. The results of this study indicate that, the average time that customers get at the time served always exceeds the standard time of service applied is 5 minutes, which is where time at 09:00-10:00 ie 5,08 minutes. Procces service always pass the standard time of service that is 5 minutes and this happens not only at certain hours but for all working hours.